2022
DOI: 10.3389/fpsyg.2021.777069
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise of Primary and Middle School Students From the Perspective of Educational Psychology and Parents’ Entrepreneurship Education

Abstract: The study aims to help primary and secondary school students develop a good habit of physical exercise by exploring the current situation of physical exercise of primary and secondary school students and analyzing the factors affecting their physical exercise. Then, intervention strategies are figured out for different groups of students and help them develop a good habit of physical exercise. From the perspective of educational psychology and parents’ entrepreneurship education, the research on the physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previous studies have discussed and confirmed the positive effects of physical exercise on the mental health of primary and middle school students or college students (e.g., Song et al, 2022;Ye et al, 2022). Thus, scholars believe that physical exercise can promote the growth of left-behind children, but lack empirical evidence to support this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have discussed and confirmed the positive effects of physical exercise on the mental health of primary and middle school students or college students (e.g., Song et al, 2022;Ye et al, 2022). Thus, scholars believe that physical exercise can promote the growth of left-behind children, but lack empirical evidence to support this claim.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of physical exercise on individuals’ mental health has become a hot topic in multiple branches of psychology (e.g., developmental psychology, health psychology, and exercise psychology). Furthermore, physical exercise plays a crucial role in preventing and adjusting children’s (or adolescents’) mental health by improving children’s sense of self-efficacy and self-esteem, reducing depression and anxiety, and enhancing their happiness ( Chi et al, 2021 ; Song et al, 2022 ). However, there are relatively few empirical pieces of literature focusing on the role of physical exercise in the mental health development of rural left-behind children, which are a critical part of a socially disadvantaged group the authors want to care about.…”
Section: Introductionmentioning
confidence: 99%
“…The academic engagement of students can be influenced by parental actions. Song et al (2022) looked at how parent participation affected the social and academic functioning. Izzo et al (1999) used a 3-year longitudinal design to examine several aspects of parent involvement, including the number of educator contacts with parents, the quality of those interactions, parents’ participation in school activities, and parents’ involvement in home activities to help their children develop socially and academically.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their failures in child care, these parents have the mindset of having the most parental control. They use both verbal and non-verbal (physical) sanctions to penalize the child’s unwanted behavior while failing to appreciate positive behavior ( Song et al, 2022 ).…”
Section: Research Literaturementioning
confidence: 99%
See 1 more Smart Citation